Shadows of Truth: Media Framing, Agenda-Setting, and the Commodification of Reality through Classical Philosophical Paradigms - Fadeji, Joseph Adabayo; Aluko, Abayomi John; Hamzat, Fatahi Owolabi (Kashere Journal of Politics and International Relations, 2025)
This paper examines how media framing, agenda-setting, and economic incentives influence the perception of truth, employing classical theories to reveal underlying dynamics. Using Plato’s Allegory of the Cave, investigate how media can shape belief systems by presenting selective "shadows" of truth, which impacts public understanding of misinformation. Linking Machiavelli’s views on power, the agenda-setting role of media highlights whose interests are served in framing specific narratives. Foucault’s ideas on power and knowledge further analyse how media constructs the notion of "fake news" to align with prevailing economic and political objectives, while Aristotle’s ethics provide insight into whether economic motives override the pursuit of societal good. Adopting the content analysis technique, the study indicates that these perspectives offer a critical framework to understand the commodification of truth and the implications of selective framing on public perception, media ethics, and governance, emphasising the need for accountability and ethical journalism.